Does Phase-Contrast Imaging through the Cerebral Aqueduct Predict the Outcome of Lumbar CSF Drainage or Shunt Surgery in Patients with Suspected Adult Hydrocephalus? - Blitz, A.M.; Shin, J.; Balédent, O.; Pagé, G.; Bonham, L.W.; Herzka, D.A.; Moghekar, A.R; Rigamonti, D. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Radiologic imaging plays a key role in diagnosing chronic adult hydrocephalus, but its role in predicting prognosis is still controversial. We sought to evaluate the effectiveness of cardiac-gated phase-contrast MR imaging through the cerebral aqueduct in predicting the clinical response to diagnostic lumbar puncture/lumbar drainage and shunt surgery in suspected adult hydrocephalus.MATERIALS AND METHODS: In this retrospective study, the phase-contrast MR imaging of 185 patients with suspected chronic adult hydrocephalus was evaluated using the CSF Flow software package. Decision-making for shunt placement was performed in this cohort on the basis of clinical assessment alone without the availability of quantitative phase-contrast MR imaging results. We recorded the response to lumbar puncture or lumbar drainage and shunt surgery using quantitative tests such as the Tinetti Test, the Timed Up and Go, and the Mini-Mental State Examination and qualitative measures of gait, urinary, and cognitive symptom improvement before and after lumbar puncture/lumbar drainage and shunt surgery. Quantitative analysis of phase-contrast MR imaging was compared with clinical outcome measures.RESULTS: Both CSF stroke volume and flow rate overlapped between lumbar puncture/lumbar drainage responders and nonresponders. There was also a significant overlap between shunt responders and nonresponders. Aqueductal stroke volume or flow rate alone was a poor predictor of lumbar puncture/lumbar drainage and shunt surgery response. Quantitative clinical measures after lumbar puncture/lumbar drainage were better predictors of shunt response.CONCLUSIONS: This study suggests that the results of phase-contrast MR imaging through the cerebral aqueduct alone should not be used to select patients for diagnostic or therapeutic CSF diversion.AQ-PCMRaqueductal phase-contrast MRICAHchronic adult hydrocephalusLDlumbar drainageLPlumbar punctureMMSEMini-Mental State ExaminationTUGTimed Up and Go